Earth's geomagnetic response to solar wind changes associated with solar events at low latitude regions at the TRE MAGDAS station - Umar, R.; Zafar, S.N.A.S.; Sabri, N.H.; Jusoh, M.H.; Yoshikawa, A.; Abe, S.; Uozumi, T. (2021)
The Sun's magnetic activity influences disturbances that perturb interplanetary space by producing large fluxes of energetic protons, triggering geomagnetic storms and affecting the ground geomagnetic field. The effect of two solar events, namely Coronal Mass Ejection (CME) and Coronal Holes, on geomagnetic indices (SYM/H), solar wind parameters and ground geomagnetic fields has provided magnetic ground data, which were extracted from the Terengganu (TRE, -4.21 N, 175.91 E) Magnetometer (MAGDAS) station, and investigated in this study. Results show that the physical dynamic mechanism in the Earth's magnetosphere is triggered by various solar wind parameters associated with CMEs and Coronal hole events during the minimum solar cycle of 24 at low latitudes. It is important to study solar wind-magnetosphere coupling because it has an impact on ground-based technological systems and human activities.